Produtividade, nutrição mineral e teores de metais pesados em milho adubado com fosfato natural e com composto de lodo de esgoto - Geraldo Ribeiro Zuba Junio (2011)
This work aimed to evaluate the effect of the fertilization with 4 doses ofsewage sludge compost and 2 of phosphate rock ones on the chemical soil attributes, contents of nutrients in the plant, and maize productivity in two successive croppings. The research was carried on Haplic Cambisol, in a design in randomized blocks with the treatments in a factorial scheme 2 x 4 correspondent to 2 doses of gafsa phosphate (0 and 90 kg ha-1 of P2O5) and 4 doses of sewage sludge compost (0; 25; 50 and 75 Mg ha-1, in dry base), with 3 replications. The productivity and macronutrients contents in the soil and in the plant, in the first and in the second successive maize cropping are not, in general, influenced by the fertilization with reactive phosphate rock, in soil contend average initial content of calcium and supplied with water from limy origin. However, they increase with the addition of sewage sludge compost to soil, being the optimum recommended dose of 75 Mg ha-1, having to be carried through new fertilization every plantation